Two Lathrobium Gravenhorst species (Coleoptera: Staphylinidae: Paederinae) new to Korea - Gae-Nam Jeon; Kee-Jeong Ahn (Journal of Asia-Pacific Biodiversity, 2023)
Two Lathrobium Gravenhorst species (L. coreanum Watanabe and L. dignum Sharp) have been documented in the Korean Peninsula. Recently, we identified two additional Lathrobium species (L. sinense Herman and L. ishiharai Hayashi) and they are reported for the first time in Korea. A key, diagnoses, and illustrations of habitus and the male genitalia of these two species are provided.